Aggressive resection of craniopharyngioma achieved by drilling the tuberculum sellae/planum sphenoidale using a frontal basal interhemispheric approach: A review of 55 cases. (January 2021) - Hu, Mengqing; Shi, Xiang'en; Liu, Fangjun; Sun, Yuming; Qian, Hai; Zhou, Zhongqing; Shi, Xiaocui
Highlights: UBIA with tuberculum sellae/planum sphenoidale drilling is an option for recurrent CP. Using water-tight microsutures of the pericranium to the defect of the sella diaphragm was effective. This method was suitable for recurrent CPs that expanded widely from intrasellar to suprasellar. The total resection of CPs by this method could be effective to reduce recurrence rate of CPs. Abstract: Objective: The frontal basal interhemispheric approach (FBIA) is preferable for resection of craniopharyngioma (CP), achieving desirable total resection rates in early reports of lesions located in the suprasellar region to the third ventricle. For tumours that have created a larger obstruction of the tuberculum sellae and planum sphenoidale, aggressive resection in the intrasellar region and medial wall of the cavernous sinus is not feasible compared to improving tumour visualization by drilling the tuberculum sellae and planum sphenoidale. In a report of drilling the sellar tuberculum and sphenoid planum, drilling allowed the direct visualization of tumours invading the intrasellar region and medial wall of the cavernous sinus. Reconstructing the opening of the sellar-sphenoid cavity is achieved by microsuturing a piece of the pericranium/dura around the dural edge of the defective dura of the open sphenoid sinus and sellar cavity to prevent cerebrospinal fluid (CSF) leakage. Patients and methods: The FBIA with drilling of the tuberculum sellae and planum sphenoidale was performed to remove the tumours that invaded the intrasellar region and cavernous sinus in 55 patients from January 2014 to October 2019 at our institution. The pre- and postoperative pituitary hormone levels and vision were evaluated as effective standards after surgery and compared using paired t -tests. The different rates of CSF leakage between the packing and microsuture groups were compared by χ 2 test, p  < 0.05. Results: In all patients with a mean 37-month follow-up (range, 3–2 months), 43 (78.2%) patients returned to their normal life or school independently, 7 (12.7%) patients were able to perform normal activities with minor complaints or effort, and 4 (7.3%) patients could care for themselves or only required occasional assistance. One (1.8%) death occurred, attributed to CSF leak-related meningitis at 5 months after surgery. Postoperative CSF leakage occurred in eight (19.0%) of 42 patients with packed bone wax or pieces of muscle to the sphenoid sinus. Of 13 patients with a piece of the periosteum/dura microsutured around the defective dura of the sellar region and open sphenoid sinus, one (7.7%) of 13 patients experienced CSF leakage in the perioperative period. With statistical analysis, there was a potential risk for postoperative CSF leakage in the bone wax and muscle piece in the open sphenoid sinus, whereas microsuture manoeuvres were effective for avoiding the risk of postoperative CSF leakage (χ 2  = 8.865, p  < 0.005). The microsutures closed the open sphenoid sinus such that it was water-tight. Postoperative visual acuity and the visual field were not affected by the increased intrasellar exposure or the open sphenoid sinus achieved by drilling the tuberculum sellae and planum sphenoidale. Conclusion: Tuberculum sellae/planum sphenoidale drilling via FBIA is feasible to enhance the direct visualization of CP resection, which expands the intrasellar region with a direct resection of recurrent tumours in the sellar cavity and adhering to the medial wall of the cavernous sinus. The potential risk of a CSF leakage seemed to be mitigated when using water-tight microsutures on a piece of the pericranium/dura around the edge of the defective dura in the sellar region and the open sphenoid sinus cavity.